Knowledge and Practice Regarding Menstruation among the Visually Challenged Female Students of Westen Nepal - Paudel, Amrita; Sah, Ram Bilakshan; Ghimire, Anup; Chakravartty, Avaniendra; Chhetri, Mamta; Bastakoti, Shankar (Annapurna Journal of Health Sciences, 2023)
Background: Menstruation is part of the female reproductive cycle starts when girls become sexually mature at the time of puberty.. A visually challenged female faces daily extra challenges for bearing their everyday skills including menstruation hygiene management. Hygienic practices during menstruation are very important as poor menstruation affects the health by increasing vulnerability to infections This study aims to assess the knowledge and practices regarding menstruation among the visually challenged female students. Methods: This cross sectional study was conducted among 121 visually challenged female students of Western Nepal who have attained the menarche. Census method was used. Descriptive and inferential statistics were used to interpret the data. Results: The mean age was 17.65 years and their age of menarche was 12.7 years. 66% falls under blindness category and 34.0% had low vision.52.9% knew about menstruation before menarche and mother was main source of information. Overall, 48.8% had good knowledge and 52.1% had satisfactory practice. Knowledge and practice were statistically significant among the visually challenged female students at p<0.05. Conclusion: In Western part of Nepal,Majority follow some forms of restriction poses in family in any forms like restriction to involve in holy activities; avoid sleeping in the bed, performing household activities. Hence, in order to break the silence of taboos, school going visually challenged students should be educated about the facts of menstruation and good hygienic practices.